Landscape as Infrastructure: Best practices for creating green urban networks to improve human and natural environments. - Moon, Michelle. (2017)
Abstract: Coming up with ideas to make a city greener is easy; actually doing them is a much greater challenge. This thesis identifies key conditions for the implementation of green infrastructure (GI). A series of three case studies shows how green techniques turn landscape into infrastructure. The studies include The Back Bay Fens in Boston's Emerald Necklace, the first constructed wetland designed for flood control; Portland's Green Streets city-wide sustainable stormwater program, which allows rain and runoff to infiltrate bioswales, thereby reducing flow to the combined sewer system; and the Atlanta Beltline's 22-mile multi-use path, a new park system that improves non-traditional infrastructure and park access. Success factors include a grand vision, collaboration, political and financial support, and good timing. This study recommends that other cities interested in GI projects should focus on collaboration, gain support from political and community leaders and groups, identify funding sources, and consider maintenance needs.; Thesis (M.A.)--Tufts University, 2011.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisors: Christine Cousineau, and Scott Horsley.; Keyword: Urban planning.